2022
DOI: 10.3390/ph15121552
|View full text |Cite
|
Sign up to set email alerts
|

Facile Entry to Pharmaceutically Important 3-Difluoromethyl-quinoxalin-2-ones Enabled by Visible-Light-Driven Difluoromethylation of Quinoxalin-2-ones

Abstract: CF2H moiety has a significant potential utility in drug design and discovery, and the incorporation of CF2H into biologically active molecules represents an important and efficient strategy for seeking lead compounds and drug candidates. On the other hand, quinoxalin-2-one is of great interest to pharmaceutical chemists as a common skeleton frequently occurring in plenty of natural products and bioactive compounds. Herein, we reported a practical and efficient protocol for the synthesis of 3-CF2H-quinoxalin-2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Additionally, a radical clock experiment revealed that rearranged product 6 from vinylcyclopropane 5 was isolated in 17% yield, along with an obviously decreased yield (18%) of 4aa (Scheme B). According to these results and our previous report, a plausible reaction mechanism was proposed in Scheme C. Initially, difluoromethylating reagent 3 is reduced by the excited-state PC* to deliver the CF 2 H radical and PC + , and then CF 2 H radical adds to ethyl acrylate 2 , leading to intermediate radical I, which sequentially adds to carbazole to render intermediate radical II, followed by a SET process to afford carbon cationic species III, along with the renewal of PC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, a radical clock experiment revealed that rearranged product 6 from vinylcyclopropane 5 was isolated in 17% yield, along with an obviously decreased yield (18%) of 4aa (Scheme B). According to these results and our previous report, a plausible reaction mechanism was proposed in Scheme C. Initially, difluoromethylating reagent 3 is reduced by the excited-state PC* to deliver the CF 2 H radical and PC + , and then CF 2 H radical adds to ethyl acrylate 2 , leading to intermediate radical I, which sequentially adds to carbazole to render intermediate radical II, followed by a SET process to afford carbon cationic species III, along with the renewal of PC.…”
Section: Resultsmentioning
confidence: 99%
“…Very recently, Wong et al explored a visible-light photoredox-catalyzed three-component reaction of quinoxalin-2(1 H )-ones, alkene, and BrCF 2 CO 2 Et to access gem -difluoromethyl-containing quinoxalin-2(1 H )-ones . In line with our continuous efforts in the development of fluoroalkylating reagents and their applications, as well as the synthesis of fluorinated biologically active compounds, the S -(difluoromethyl)sulfonium salt developed by our group has proved to be a good difluoromethyl radical ( • CF 2 H) precursor and could be applied to a wide variety of • CF 2 H transformations. We herein report a facile and practical approach for the synthesis of CF 2 H-containing carbazoles via a visible-light photoredox-catalyzed three-component reaction of carbazoles with styrenes and S -(difluoromethyl)sulfonium salt (Scheme c), and a broad range of fluoroalkyl-functionalized carbazole derivatives were readily synthesized in moderate to good yields by mild visible-light-photoredox catalysis.…”
Section: Introductionmentioning
confidence: 89%
“…The reductive quenching of the excited dia- Quinoxalin-2-ones 137 can also be effectively subjected to a difluoromethylation process using a visible-light redox-catalysed reaction in the presence of a photocatalyst, specifically tetrakis(4-(tert-butyl)phenyl)anthracene-9,10-diamine, and S-(difluoromethyl)sulfonium salt 140 as a source of difluoromethyl radicals (Scheme 65). 118 This results in the formation of structurally diverse 3-difluoromethyl-quinoxalin-2-ones 139, likely through a radical mechanism. The difluoromethylating agent 140 is reduced by the excited-state PC* to yield the CF 2 H radical and PC + .…”
Section: Aromatic C-h Functionalisationmentioning
confidence: 99%
“…Notably, S -(difluoromethyl) sulfonium salt 14 developed by us has proven to be a highly efficient difluoromethyl radical precursor under visible-light irradiation. 15 In line with our continuous research interest in fluoroalkylating reagents, and their synthetic applications in the assembly of fluorinated biologically active compounds, 15–18 we herein present a facile and practical approach to accessing difluoromethylated oxindoles and isoquinoline-1,3-diones from N -acrylamides. This protocol involved a visible-light photoredox-catalyzed cascade difluoromethylation/cyclization process with S -(difluoromethyl)sulfonium salt (Scheme 1d), and a vast array of CF 2 H-containing oxindoles and isoquinoline-1,3-diones were readily accessed in good to excellent yields under mild reaction conditions.…”
mentioning
confidence: 94%